Analiza tržne naravnanosti podjetij v Sloveniji - Gabrijan, Vladimir (Akademija MM, 1998)
In countries in transition we often speak about the necessity of market orientation of companies as one of the most important factors for a successful entrance into the world of normal economies. Unfortunately, market orientation in these countries is more often a generalized and unverified topic for discussion than a matter of profound empirical research. In our contribution the results of measuring market orientation of Slovene companies are given. The investigated companies were segmented according to the type of ownership and capital.
Keywords: corporation; konkurenca; konkurenčnost; podjetje; Slovenia; Slovenija; trg; trženje; tržno gospodarstvo